Trends in hospitalizations for diagnosed congenital cytomegalovirus in infants and children in Australia - MacIntyre C Raina; Booy Robert; Seale Holly (BMC, 2009)
Abstract Background Cytomegalovirus (CMV) is responsible for a wide range of diseases in neonates, and has been recognized as a major cause of congenital defects in developed countries for many years. More children suffer serious disabilities caused by congenital CMV than by several better-known childhood maladies. Insight into the epidemiology of congenital CMV disease is needed for the assessment of preventive strategies. Methods Using data from the National Hospital Morbidity Database (NHMD) complied by the Australian Institute of Health and Welfare (AIHW), we examined the rates of hospital admissions for children diagnosed with congenital cytomegalovirus (CMV) by year, sex, age group and length of stay. Results Over an 8-year period (1993-2001), there were 1314 admissions for the congenital form of CMV disease. Of these admissions, 25% were principally hospitalized because of congenital CMV. The average annual rate of admissions in children aged 0-4, 5-9 and 10-14 years was 9.40, 2.40 and 0.85 per 100,000 Australian population respectively. Conclusion Compared with many other congenital illnesses, which are now vaccine preventable, the burden of congenital CMV is comparatively high. A vaccination program would be justifiable should a vaccine become available.